PENGARUH PERTUMBUHAN EKONOMI TERHADAP KESEJAHTERAAN KELUARGA BUKAN PEGAWAI NEGERI SIPIL DI SURABAYA - Fachrudy Asjari (Fakultas Ekonomi Universitas PGRI Adi Buana, 2015)
This research intended to analyze the economic growth and family welfare. The implications on economic growth and welfare in this framework, it is driven by economic growth.This research was conducted in Surabaya which covered 105 supervisors as respondent. This research by utilizing Regression, the technique was processed with SPSS20 to analyze hypothesis.The inter correlations models between these variables in this study revealed that the hypothesis have significant correlation.The result of this research were empirical date of the development of the theoretical of economic science.